2021
DOI: 10.1002/mame.202000814
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of High Strength and Toughness Aramid Fiber by Introducing Flexible Asymmetric Monomer to Construct Misplaced‐Nunchaku Structure

Abstract: High performance fibers with high strength and toughness have great potential in composites, but contradiction between tensile strength and elongation at break makes the preparation to become a current challenge. Herein, an asymmetric structure of more flexible diamine, 3,4′‐diaminodiphenyl ether (3,4′‐ODA), is introduced into heterocyclic aramid (PBIA) fibers to replace rigid symmetric p‐phenylenediamine (PDA). By studying the properties of copolymer (mPEBA) fibers with different ratios of diamine, it is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…108 As a result, it can act as an effective method in increasing toughness and maximum strain. 109 Following a similar strategy, in previous studies, it was shown that ODA with flexible –O– linkage can easily bend when the free rotation of the ether bond takes place. 109 This can explain the more flexible characteristic of the S1M sample compared to S2M.…”
Section: Resultsmentioning
confidence: 94%
“…108 As a result, it can act as an effective method in increasing toughness and maximum strain. 109 Following a similar strategy, in previous studies, it was shown that ODA with flexible –O– linkage can easily bend when the free rotation of the ether bond takes place. 109 This can explain the more flexible characteristic of the S1M sample compared to S2M.…”
Section: Resultsmentioning
confidence: 94%
“…As previously mentioned, aramid polymers are generally not characterized via GPC due to their stark insolubility in all organic solvents, with few reported exceptions. ,, The soluble compounds typically require laborious syntheses to prepare monomers that impart some solubility to the aramid product in organic solvents. We were delighted to find an additive that provided partial or full solubility at 3 mg/mL of most of our polymeric analogues, which enabled GPC-SEC characterization of at least some of our polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Several effective approaches were applied to improve the solubility of aromatic polyamide, including the introduction of flexible structural units, [20][21][22] largevolume side groups, [23,24] asymmetric structures, [25,26] or polar side groups to the backbone, [27][28][29] and the copolymerization monomers having nonplanar structures. [30,31] In addition, several methods also have been developed to improve the flexibility of PMIA.…”
Section: Introductionmentioning
confidence: 99%